Pendekatan Ekologis terhadap Variasi Populasi Hama dan Pengaruhnya terhadap Pertumbuhan Jagung - Yassin, Haykal (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to explore the ecological dynamics of pest populations and their impact on the growth of maize (Zea mays L.) in tropical regions. Conducted in Central Lombok Regency—one of the major maize-producing areas in West Nusa Tenggara—the research combines quantitative field surveys with ecological analysis to investigate the relationship between environmental factors and pest activity. Two dominant pest species, Stenocranus pacificus and Spodoptera frugiperda, were observed through population density measurements, climatic condition monitoring, and crop management evaluations. The results indicate that pest fluctuations are significantly influenced by temperature, humidity, and plant spacing. High pest density adversely affects plant height, number of productive leaves, and leaf area. These findings emphasize the importance of ecosystem-based pest management as a preventive and adaptive strategy to maintain sustainable maize productivity in tropical agricultural systems.